The luxury car tax: past its use-by date - Pearce, Prafula (Taxation Institute of Australia, 2013)
There are increasing calls to abolish the luxury car tax (LCT) as it has passed its “use-by” date. The tax has been singled out as an unfair, a discriminatory and an inequitable tax that discourages innovation in the manufacture of environmentally friendly vehicles. Following the recommendations from the Henry Tax Review and the discussions at the 2011 Tax Forum on environmental and social taxes, the reform of the LCT could form part of a wider review of motor vehicle taxes and fuel excise in Australia. A tax on the purchase of motor vehicles could be structured to bring about a behavioural change in the choice of motor vehicles in order to reduce fuel consumption in motor vehicles, provide a competitive edge to the Australian motor vehicle industry, and generate the revenues required to build better public transport infrastructure.